The impact of disc degeneration on the dynamic characteristics of the lumbar spine: a finite element analysis - Wang, Xue; Liu, Wei; Zhao, Yaqiong; Ma, Pengcheng (Frontiers in Bioengineering and Biotechnology, 2024)
The dynamics of disc degeneration was analyzed to determine the effect of disc degeneration at the L4-L5 segment on the dynamic characteristics of the total lumbar spine. A three-dimensional nonlinear finite element model of the L1-S1 normal lumbar spine was constructed and validated. This normal model was then modified to construct two degeneration models with different degrees of degeneration (mild, moderate) at the L4-L5 level. Modal analysis, harmonic response analysis, and transient dynamics analysis were performed on the total lumbar spine when experiencing following compressive loading (500 N). As the degree of disc degeneration increased, the vibration patterns corresponding to the first three orders of the model's intrinsic frequency were basically unchanged, with the first order being in the left-right lateral bending direction, the second order being in the forward-flexion and backward-extension direction, and the third order being in the axial stretching direction. The nucleus pulposus pressure peaks corresponding to the first order intrinsic frequency for the harmonic response analysis are all on the right side of the model, with sizes of 0.053 MPa, 0.061 MPa, and 0.036 MPa, respectively; the nucleus pulposus pressure peaks corresponding to the second order intrinsic frequency are all at the rear of the model, with sizes of 0.13 MPa, 0.087 MPa, and 0.11 MPa, respectively; and the nucleus pulposus pressure peaks corresponding to the third order intrinsic frequency are all at the front of the model, with sizes of 0.19 MPa, 0.22 MPa, and 0.22 MPa, respectively. The results of the transient analysis indicated that over time, the response curves of the healthy model, the mild model, and the moderate model all exhibited cyclic response characteristics. Intervertebral disc degeneration did not adversely affect the vibration characteristics of the entire lumbar spine system. Intervertebral disc degeneration significantly altered the dynamics of the degenerative segments and their neighboring normal segments. The process of disc degeneration gradually shifted the load from the nucleus pulposus to the annulus fibrosus when the entire lumbar spine was subjected to the same vibratory environment.